Sikap Mahasiswa terhadap Teman Sebaya Berkebutuhan Khusus pada Perguruan Tinggi di Indonesia - Dominika Arthalia Ayunda Putri; Farida Kurniawati (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2022)
This study is aimed to see the attitude towards person with disabilities of college students in Indonesia. Currently, the implementation of inclusive education has spread to the higher educational level. However, not all universities are ready to accept the presence of person with disabilities as campus residents. Various studies show different results regarding attitudes towards person with disabilities. This study used a quantitative approach with a questionnaire as a data collection tool. The questionnaire used were Multidimensional Attitudes toward Person with Disabilities (MAS). Analysis of attitude towards person with disabilities is seen as a single variable in this descriptive study. Participants in this study were college students in vocational or undergraduate program in Indonesia. The participants used in the data analysis were 530 people. The results showed that the attitude towards disabilities in Indonesia college students have positive attitudes (M1 = 3.36, M2 = 3.24, M3 = 3.63, M4 = 3.27). All components of the attitude shown by all respondents showed positive results. It is expected that college students show a positive attitude both cognitively, emotionally, and behaviorally, and can accept persons with disabilities as part of the campus community and minimize discrimination that occurs in the campus area against persons with disabilities.